2007
DOI: 10.1111/j.1540-8183.2007.00212.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Results (Up to 16.5 Years) of Mitral Balloon Valvuloplasty in a Series of 518 Patients and Predictors of Long‐Term Outcome

Abstract: MBV provides excellent long-term results for selected patients with MS. The long-term outcome after this procedure can be predicted from baseline clinical and echocardiographic characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 31 publications
0
17
1
Order By: Relevance
“…In the National Heart, Lung Blood Institute Balloon Valvotomy Registry of 736 patients, [15] the MVA by echocardiographic assessment was 1.09 6 0.29 cm 2 before the procedure and increased to 1.8 6 0.15 cm 2 after the procedure. In the author's series of 518 patients [14] the echocardiographic MVA was 0.92 6 0.17 cm 2 before the procedure, and increased to 2.0 6 0.29 cm 2 after the procedure. A significant inverse relationship was found between the echo score and post procedure MVA where mitral valve morphology was found to be a strong predictor of post procedure mitral opening [13][14][15][16].…”
Section: Immediate Hemodynamic Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…In the National Heart, Lung Blood Institute Balloon Valvotomy Registry of 736 patients, [15] the MVA by echocardiographic assessment was 1.09 6 0.29 cm 2 before the procedure and increased to 1.8 6 0.15 cm 2 after the procedure. In the author's series of 518 patients [14] the echocardiographic MVA was 0.92 6 0.17 cm 2 before the procedure, and increased to 2.0 6 0.29 cm 2 after the procedure. A significant inverse relationship was found between the echo score and post procedure MVA where mitral valve morphology was found to be a strong predictor of post procedure mitral opening [13][14][15][16].…”
Section: Immediate Hemodynamic Resultsmentioning
confidence: 96%
“…In the author's series of 518 patients [14] the echocardiographic MVA was 0.92 6 0.17 cm 2 before the procedure, and increased to 2.0 6 0.29 cm 2 after the procedure. A significant inverse relationship was found between the echo score and post procedure MVA where mitral valve morphology was found to be a strong predictor of post procedure mitral opening [13][14][15][16]. However, good results could also be obtained in cases with relatively high echo score.…”
Section: Immediate Hemodynamic Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…They found that favorable valve anatomy, age, and postprocedural mitral valve area were predictors of event-free survival. 42 Iung et al 43 reported an event-free survival (survival with freedom from repeat PMBV, mitral valve replacement, cardiac death, high NYHA class) rate of 61% at 10 years in Ͼ1000 patients (mean age 49Ϯ14 years) with successful PBMV. Although favorable long-term prognosis largely depends on immediate procedural success, the prediction of late prognosis includes multiple factors including old age, unfavorable valve anatomy, high NYHA class, atrial fibrillation, low valve area after PBMV, high gradient after PBMV, and Ͼgrade 2 mitral regurgitation after PBMV.…”
Section: Long-term Resultsmentioning
confidence: 99%